Prognostic factors for death and survival with or without complications in cardiac arrest patients receiving CPR within 24 hours of anesthesia for emergency surgery - Siriphuwanun,V. (Dove Medical Press Ltd., 2015)
© 2014 Siriphuwanun et al. Purpose: To determine prognostic factors for death and survival with or without complications in cardiac arrest patients who received cardiopulmonary resuscitation (CPR) within 24 hours of receiving anesthesia for emergency surgery. Patients and methods: A retrospective cohort study approved by the Maharaj Nakorn Chiang Mai University Hospital Ethical Committee. Data used were taken from records of 751 cardiac arrest patients who received their first CPR within 24 hours of anesthesia for emergency surgery between January 1, 2003 and October 31, 2011. The reviewed data included patient characteristics, surgical procedures, American Society of Anesthesiologist (ASA) physical status classification, anesthesia information, the timing of cardiac arrest, CPR details, and outcomes at 24 hours after CPR. Univariate and polytomous logistic regression analyses were used to determine prognostic factors associated with the outcome variable. P-values of less than 0.05 were considered statistically significant. Results: The outcomes at 24 hours were death (638/751, 85.0%), survival with complications (73/751, 9.7%), and survival without complications (40/751, 5.3%). The prognostic factors associated with death were: age between 13-34 years (OR =3.08, 95% CI =1.03-9.19); ASA physical status three and higher (OR =6.60, 95% CI =2.17-20.13); precardiopulmonary comorbidity (OR =3.28, 95% CI =1.09-9.90); the condition of patients who were on mechanical ventilation prior to receiving anesthesia (OR =4.11, 95% CI =1.17-14.38); surgery in the upper abdominal site (OR =14.64, 95% CI =2.83-75.82); shock prior to cardiac arrest (OR =6.24, 95% CI =2.53-15.36); nonshockable electrocardiography (EKG) rhythm (OR =5.67, 95% CI =1.93-16.62); cardiac arrest occurring in postoperative period (OR =7.35, 95% CI =2.89-18.74); and duration of CPR more than 30 minutes (OR =4.32, 95% CI =1.39-13.45). The prognostic factors associated with survival with complications were being greater than or equal to 65 years of age (OR =4.30, 95% CI =1.13-16.42), upper abdominal site of surgery (OR =10.86, 95% CI =1.99-59.13), shock prior to cardiac arrest (OR =3.62, 95% CI =1.30-10.12), arrhythmia prior to cardiac arrest (OR =4.61, 95% CI =1.01-21.13), and cardiac arrest occurring in the postoperative period (OR =3.63, 95% CI =1.31-10.02). Conclusion: The mortality and morbidity in patients who received anesthesia for emergency surgery within 24 hours of their first CPR were high, and were associated with identifiable patient comorbidity, age, shock, anatomic site of operation, the timing of cardiac arrest, EKG rhythm, and the duration of CPR. EKG monitoring helps to identify cardiac arrest quickly and diagnose the EKG rhythm as a shockable or nonshockable rhythm, with CPR being performed as per the American Heart Association (AHA) CPR Guidelines 2010. The use of the fast track system in combination with an interdisciplinary team for surgery, CPR, and postoperative care helps to rescue patients in a short time.